Skin and other stories - Dahl, Roald (Puffin London, 2013)
This is a collection of eleven short stories to startle, surprise and satisfy from Roald Dahl - the master of the twist in the tale. How would you get rid of a murder weapon without causing suspicion? Where would you hide a diamond where no one else would think of looking? What if you found out the tattoo on your back was worth over a million pounds?